Worldview studies. Issue 3 (September 2022) - Stenmark, Mikael
Abstract: I argue that philosophers of religion should not merely focus on religions but should pay much more attention to the secular outlooks on life emerging in contemporary society. To compare these outlooks, I suggest that we use the notion of worldview, and contrast religious worldviews with secular worldviews − rather than contrasting religions with nonreligions, which scholars of religion have recently tended to do. Accordingly, religious people should be contrasted with secular people and not with religious 'nones'. I also explore the specific contribution of philosophy of religion to worldviews studies, and discuss why such a contribution is considered controversial within religious studies circles. I contend that it should instead be a legitimate and essential part of the academic study of worldviews.